A Case Report of Wolf’s Post-Herpetic Isotopic Response: Herpetiform Pemphigus - Tang S; Wang L; Liu Y; Liu L; Deng J; Guo G; Liu H; Wen C; Wu R (Journal of Inflammation Research)
Shanshan Tang,1,* Lanying Wang,2,* Yuetong Liu,2 Lanxin Liu,2 Jiqing Deng,2 Guixian Guo,2 Haiyan Liu,2 Changhui Wen,1 Ran Wu1 1Department of Dermatology, The First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, 550001, People’s Republic of China; 2Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, 550002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ran Wu, Department of Dermatology, The First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou, 550001, People’s Republic of China, Email wuranshou@126.comPurpose: To report a rare case of Wolf’s post-herpetic isotopic response (PHIR) manifesting as herpetiform pemphigus (HP) after herpes zoster (HZ) infection and explore its potential pathogenesis.Patients and Methods: A 76-year-old male patient with a history of HZ on the right lateral waist, abdomen, and back. Fifteen days after the cure of HZ, annular erythema, blisters, and pruritus appeared at the original site of the same skin lesions and then spread throughout the body. Retrospective analysis was performed through clinical examination, histopathology, direct immunofluorescence, and autoantibody detection.Results: The patient was diagnosed with PHIR presenting as HP based on medical history and test results. Treatment with methylprednisolone (initial dose 40 mg/day) and antibiotics resolved lesions within 2 weeks, with no recurrence during 18 months of follow-up. The pathogenesis was hypothesized to involve local and systemic immune microenvironment changes induced by varicella-zoster virus (VZV) infection.Conclusion: HP developing after HZ may represent a novel manifestation of PHIR, providing new evidence for this phenomenon. Clinicians should consider immune-related bullous diseases in post-HZ skin lesions. Larger studies are needed to validate the association between viral infection and immune imbalance in pathogenesis.Keywords: Wolf’s post-herpetic isotopic response, herpes zoster, herpetiform pemphigus, varicella-zoster virus infection